ANALISIS DAMPAK PERUBAHAN FEED STOCK NATURAL GAS - Melany Adelia; Febri Sinta Marito Panjaitan; Muhammad Husaini Zaidan; Nova Yoga Pradana; Imam Karfendi Putro; Ibnu Eka Rahayu (Politeknik Negeri Samarinda, 2022)
K company is a petrochemical industry that utilizes natural gas as a raw material to produce methanol with AA grade with a purity above 99.85%. In general, PT K's methanol production undergoes four main processes, such desulphurizing, reforming, methanol synthesis and distillation. The natural gas used by PT K underwent a change in composition due to new wells upstream entering PT K in 2017. The natural gas entering PT K has a leaner composition (containing more CH4) and also has a lower sulfur content which causes a decrease in production at PT K. Keywords: Methanol Grade AA, Natural Gas, lean gas, Sulfur